2020
DOI: 10.3389/fpls.2020.585510
|View full text |Cite
|
Sign up to set email alerts
|

Host Plant Resistance to Bemisia tabaci to Control Damage Caused in Tomato Plants by the Emerging Crinivirus Tomato Chlorosis Virus

Abstract: Tomato chlorosis virus (genus Crinivirus, family Closteroviridae) (ToCV) is rapidly emerging, causing increased damage to tomato production worldwide. The virus is transmitted in a semipersistent manner by several whitefly (Hemiptera: Aleyrodidae) species and is expanding its geographical and host ranges associated with the emergence of whiteflies of the Bemisia tabaci complex. Control is based essentially on intensive insecticide applications against the insect vector but is largely ineffective. No virus-resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 40 publications
(58 reference statements)
0
9
0
1
Order By: Relevance
“…With the development of high-throughput sequencing technology, it has become widely used in the studies of plant-virus interactions ( Ding et al, 2019 ; Şahin-Çevik et al, 2019 ; Fortes et al, 2020 ), and there have been a lot of plant-virus interactions in tomato plants, but most of them are concentrated on tomato yellow leaf curl virus (TYLCV) and related DNA viruses ( Chen et al, 2013 ; Lucioli et al, 2016 ; Sahu et al, 2020 ). Although much research has focused on the identification of related resistance genes, it has always been a challenge to determine resistance genes so that they can be introduced into tomato plants.…”
Section: Discussionmentioning
confidence: 99%
“…With the development of high-throughput sequencing technology, it has become widely used in the studies of plant-virus interactions ( Ding et al, 2019 ; Şahin-Çevik et al, 2019 ; Fortes et al, 2020 ), and there have been a lot of plant-virus interactions in tomato plants, but most of them are concentrated on tomato yellow leaf curl virus (TYLCV) and related DNA viruses ( Chen et al, 2013 ; Lucioli et al, 2016 ; Sahu et al, 2020 ). Although much research has focused on the identification of related resistance genes, it has always been a challenge to determine resistance genes so that they can be introduced into tomato plants.…”
Section: Discussionmentioning
confidence: 99%
“…Trichomes are physical barriers to indirect plant defense mechanisms against insects with toxic and other harmful effects (War et al, 2012). This is in line with the study of Fortes, Fernández-Muñoz, & Moriones (2020), leaf glandular trichomes are useful to control the persistent transmitting of begomovirus Tomato Yellow Leaf Curling (TYLCV) which is infected by a vector Bemisia tabaci. Moreover, trichome consisted of acylsucroses that has a negative effect on B.tabaci.Correlation analysis (Table 2) revealed that the density of trichomes was negatively correlated with the percentage of Helopeltis damage (r = −0.368).…”
Section: Resultsmentioning
confidence: 64%
“…Tanaman tomat dengan acylsugars tinggi menyebabkan oviposisi kutukebul yang lebih rendah dan jumlah nimfa yang lebih sedikit dibandingkan dengan genotipe dengan kandungan acylsugars yang rendah (Neiva et al 2018). Tomat yang tahan B. tabaci, memproduksi acylsugars secara efektif mampu mengendalikan penyebaran ToCV dibandingkan dengan galur yang hampir isogenik tanpa trikoma tipe IV dan sekresi acylsugars (Fortes et al 2020). Perilaku makan utama kutukebul saat inokulasi virus tergantung pada aktivitas stiletnya dalam sieve element (elemen tipis) (Maluta et al 2017).…”
Section: Pembahasanunclassified